Analisis Efisiensi Efektivitas Penerimaan Pajak Daerah Dan Retribusi Daerah Dalam Rangka Optimalisasi Penerimaan Pendapatan Asli Daerah Kabupaten Hulu Sungai Selatan (Periode 2009 Sampai Dengan 2018) - Ainaya Al Fatihah; Saleh, Muhammad (PPJP ULM, 2020)
The pu ose of this study is to determine the rate of efficiency and effectiveness ofregional tax revenue in the Hulu Sungai Selatan Regency and to determine the rate ofgrowth and its contribution to regional taxes and regional own-source revenue (PAD)of the Hulu Sungai Selatan Regency. Local tax as one component of local revenuecontained in the original regional income imposed on the residents of the area by theregional government without obtaining direct contra from the tax paid.The method used in this research is a quantitative descriptive study with theanalysis method of efficiency, effectiveness, contribution and growth rate usingsecondary data in the form of the realization of the regional income and expenditurebudget obtained from the Regional Finance Agency of the South Hulu Sungai Regency.